Ocular involvement in TEMPI syndrome - Jo-Hsuan Wu; Narine Viruni; Justin Chun; Satish Shanbhag; T.Y. Alvin Liu (American Journal of Ophthalmology Case Reports, 2022)
Purpose: We report the first case of ocular involvement in TEMPI syndrome, a rare disease characterized by telangiectasias, elevated erythropoietin with erythrocytosis, monoclonal gammopathy, perinephric fluid collections, and intra-pulmonary shunting. Observations: A 64-year-old Caucasian man with history of TEMPI syndrome presented with subacute bilateral painless vision loss. Ocular examination showed chronic retinal ischemia with microvascular damage, which was likely associated with the chronic systemic hypoxemia, and spontaneous wax and wane of cystoid macular edema, presumedly related to the systemic bortezomib treatment. Conclusions and importance: Our case demonstrates that pathologic retinal vascular changes could be seen in association with TEMPI syndrome and suggests that a comprehensive ophthalmological examination may be beneficial for these patients.